'Am I being unreasonable to vaccinate my kids against my ex's wishes?' – A corpus linguistic exploration of conflict in vaccination discussions on Mumsnet Talk's AIBU forum. (August 2022) - Coltman-Patel, Tara; Dance, William; Demjén, Zsófia; Gatherer, Derek; Hardaker, Claire; Semino, Elena
Highlights: Mumsnet's forum Am I Being Unreasonable (AIBU) is particularly confrontational. Original poster's (OP) vaccination decisions challenged by family or friends. Social dynamics and family relations are an important aspect of vaccine hesitancy. Insults in replies target anti-vaccination family or friends of a pro-vaccination OP. Insults may support pro-vaccination attitudes but also contribute to polarisation. Abstract: Online parenting forums are popular sources of information about childhood vaccinations, but vaccination discussions, especially online, are often polarised and polarising (Jenkins & Moreno 2020). This can have very real implications for ultimate vaccination decisions (Al-Hasan et al., 2021). Among the most visited parenting forums in the UK is Mumsnet Talk, hosted on the parenting website Mumsnet, which has a reputation for being straight-talking and combative. This supposedly applies particularly to its most popular Talk Topic, Am I being unreasonable?' (AIBU), which also includes numerous threads related to vaccinations. In this paper we combine corpus-based methods with qualitative discourse analysis to examine over 6-million words of vaccination-related discussions on 895 threads on AIBU from the inception of Mumsnet in 2000 to May 2021. We provide evidence of a greater presence of confrontation-related language in these threads when compared with similar threads not on AIBU, zooming in on nine keywords that can be used as insults (e.g. 'idiot' and 'bitch'). The use of these keywords reveals the multiple types of conflict at play, including between people with opposing and similar vaccine stances. While some insults are directed at each other within the forum, the majority are directed at external third parties, often the protagonists at the heart of offline conflicts detailed in the original post of an AIBU thread. We show that, although these insults perform impoliteness towards external third parties potentially perpetuating conflict that predates any posting on the forum, they simultaneously have a supportive and community enhancing function within the threads. We reflect on the implications of our findings for the role of AIBU as a point of reference and site of interaction for parents facing vaccination-related issues and decisions.